Installation of aluminium cladding / Mohamad Aqmal Mohamed Johar Fikri - Mohamed Johar Fikri, Mohamad Aqmal (Universiti Teknologi MARA, Perak, 2014)
This report described about fabrication and installation of aluminium cladding to built a new headquarters of Kuantan Municipal Council. This report was reported based on the observation and experience of five month at the construction project. This report is divided into several of parts beginning with an introduction, company background, case study, conclusion and suggestion. From the observation the maintenance process of fabrication and installation is very simple but only certain person can do it. This report, described about identifying and understanding the equipment, machineries and material used in completing fab1ication of aluminium cladding. Beside that to identify the process before installation the aluminium cladding and determine the method of construction for aluminium cladding applied specifically for high rise building.